Dietary Zinc Requirement of Young Giant Gouramy (Osphronemus gouramy, Lac.) - Mia Setiawati; N.R. Azwar; I. Mokoginta; R. Affandi (Jurnal Akuakultur Indonesia)
This experiment was conducted to determine the dietary zinc requirement of young giant gouramy. Five experimental diets were used in this experiment containing iso-nitrogenous and iso-energy with different levels of zinc (0, 25, 50, 100, and 200 mg per kg). The initial means of body weight of body the fishes was 0.82 g per individual. The fishes were fed upon the diets at satiation, three times daily, for 12 weeks. The results indicated no zinc deficiency symptoms in this experiment. The daily growth rate, feed efficiency, survival rates and protein and lipid retention were not significantly different from all the diets. However, fish fed upon 25 mg Zn/kg diets produced the highest protein and total digestibility. The zinc contents of 25 mg Zn/kg diets gave the highest value in zinc accumulation in the bone, blood serum and eyes. The highest accumulation of the zinc in the liver occurred in 50 mg Zn/kg diets. There was increase in zinc content of the tissues after increasing levels of dietary zinc. Thus, Zn requirement for juvenile of giant gouramy was 25-50 mg/kg diets.